Telemedicine in the management of temporomandibular disorders: A literature review - Chairunnisa, Ricca; Shabrina, Aliyya; Sukotjo, Cortino (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Temporomandibular disorders are clinical disorders involving the muscles of mastication, temporomandibular joints, and related structures. There are several treatments, such as self-help exercises, that can be done at home using remote care, often called telemedicine, after the patient has been directed to do so by a practitioner and evaluated during regular visits. Along with advancement of the times and technology, as well as with the prevention of COVID-19, telemedicine may currently be the main means of self-care for patients at home without losing the supervision of a doctor. Purpose: The purpose of this study is to determine the effect of using telemedicine in the management of temporomandibular disorders. Methods: A systematic literature review was undertaken using literature search methods in electronic databases: PubMed, ProQuest, and Google Scholar. The keywords were